Comparative Genomics of Gene Expression in the Parasitic and Free-Living Nematodes Strongyloides stercoralis and Caenorhabditis elegans - Mitreva, Makedonka; McCarter, James P.; Martin, John; Dante, Mike; Wylie, Todd; Chiapelli, Brandi; Pape, Deana; Clifton, Sandra W.; Nutman, Thomas B.; Waterston, Robert H. (Genome Research, 2004)
Although developmental timing of gene expression is used to infer potential gene function, studies have yet to correlate this information between species. We analyzed 10,921 ESTs in 3311 clusters from first- and infective third-stage larva (L1, L3i) of the parasitic nematode Strongyloides stercoralis and compared the results to Caenorhabditis elegans, a species that has an L3i-like dauer stage. In the comparison of S. stercoralis clusters with stage-specific expression to C. elegans homologs expressed in either dauer or nondauer stages, matches between S. stercoralis L1 and C. elegans nondauer-expressed genes dominated, suggesting conservation in the repertoire of genes expressed during growth in nutrient-rich conditions. For example, S. stercoralis collagen transcripts were abundant in L1 but not L3i, a pattern consistent with C. elegans collagens. Although a greater proportion of S. stercoralis L3i than L1 genes have homologs among the C. elegans dauer-specific transcripts, we did not uncover evidence of a robust conserved L3i/dauer `expression signature.' Strikingly, in comparisons of S. stercoralis clusters to C. elegans homologs with RNAi knockouts, those with significant L1-specific expression were more than twice as likely as L3i-specific clusters to match genes with phenotypes. We also provide functional classifications of S. stercoralis clusters.
10.1101/gr.1524804